Saccharomyces cerevisiae CNCM I-3856 as a New Therapeutic Agent Against Oropharyngeal Candidiasis - Roselletti, Elena; Sabbatini, Samuele; Ballet, Nathalie; Perito, Stefano; Pericolini, Eva; Blasi, Elisabetta; Mosci, Paolo; Cayzeele Decherf, Amélie; Monari, Claudia; Vecchiarelli, Anna (Frontiers in Microbiology, 2019)
Oropharyngeal candidiasis is a common opportunistic mucosal infection of the oral cavity, mainly caused by an overgrowth of Candida albicans. This infection can inhibit nutritional intakes and strongly affect quality of life. To date, standard therapeutic strategies involving the administration of antifungal drugs can bring several side-effects, not least the emergence of drug-resistant strains. The purpose of this study is to investigate the effectiveness of Saccharomyces cerevisiae CNCM I-3856 (live or inactivated cells) against oropharyngeal candidiasis. Our results show that administration of S. cerevisiae CNCM I-3856 (live or inactivated cells) in the oral cavity of C57BL/6J mice resulted in a protective effect against oropharyngeal candidiasis. The strongest effect was obtained with live S. cerevisiae CNCM I-3856. This was related to: i) a decrease of C. albicans load in the oral cavity, esophagus, stomach and duodenum; ii) an early resolution of inflammatory process in the tongue; iii) a marked reduction of C. albicans virulence factors; and iv) a consistent increase of neutrophils antimicrobial capacity. These findings suggest that S. cerevisiae products are potentially beneficial in the treatment of oropharyngeal candidiasis.